Skyrmions in twisted bilayer graphene: stability, pairing, and crystallization - Kwan, YH; Wagner, G; Bultinck, N; Simon, SH; Parameswaran, SA (American Physical Society, 2022)
We study the excitations that emerge upon doping the translationally invariant correlated insulating states in magic-angle twisted bilayer graphene at various integer filling factors ν. We identify parameter regimes where these are excitations associated with skyrmion textures in the spin or pseudospin degrees of freedom, and explore both short-distance pairing effects and the formation of long-range ordered skyrmion crystals. We perform a comprehensive analysis of the pseudospin skyrmions that emerge upon doping insulators at even ν, delineating the regime in parameter space where these are the lowest-energy charged excitations by means of self-consistent Hartree-Fock calculations on the interacting Bistritzer-MacDonald model. We explicitly demonstrate the purely electron-mediated pairing of skyrmions, a key ingredient behind a recent proposal of skyrmion superconductivity. Building upon this, we construct hopping models to extract the effective masses of paired skyrmions, and discuss our findings and their implications for skyrmion superconductivity in relation to experiments, focusing on the dome-shaped dependence of the transition temperature on the twist angle. We also investigate the properties of spin skyrmions about the quantized anomalous Hall insulator at ν=+3. In both cases, we demonstrate the formation of robust spin or pseudospin skyrmion crystals upon doping to a finite density away from integer filling.